A comparison of electrocardiographic parameters in e-cigarette users, conventional cigarette smokers, and non-smokers - Heba Ammar; Rania Hashish; Shrouk Mohamed Ali; Ahmed Salah Salem; Abeer Mohamed Hagras (SpringerOpen, 2024)
Abstract Background Smoking is a major preventable risk factor for cardiovascular morbidity and mortality. Tobacco smoking induces atherosclerosis, ischemic heart diseases, and arrhythmias. The impact of electronic cigarettes on cardiovascular health is still controversial. This study aimed to evaluate the electrocardiographic parameters in chronic electronic cigarette users compared to chronic conventional cigarette smokers and a non-smoker control group of matched age and gender. Results The study involved 105 volunteers with no history of chronic or cardiovascular diseases or cardioactive drug use. Participants were assigned into three study groups, chronic e-cigarette users, conventional cigarette smokers, and non-smokers, each consisting of 35 participants. Demographic data, smoking history, vital signs, and 12-lead electrocardiogram (ECG) were evaluated. Demographic data were insignificantly different among all study groups. The mean heart rate was significantly higher in chronic electronic cigarette users and conventional cigarette smokers compared to non-smokers (p < 0.001).QRS complex duration was significantly shorter in e-cigarette users and conventional smokers compared to non-smokers (p < 0.001). Prolonged QT and QTc intervals duration were recorded in e-cigarette users and conventional smokers compared to non-smokers (p < 0.001). All the ventricular repolarization indices (T wave-peak to T-end (Tpe) interval, TPe/QT ratio, and TPe/QTc ratio were significantly prolonged in chronic e-cigarette users, and conventional smokers compared to non-smokers (p < 0.001). Mean systolic, diastolic blood pressure, P wave amplitude and duration, and PR interval were insignificantly different between all groups (P > 0.05). Conclusions Chronic e-cigarette use is associated with higher heart rates, shorter QRS complex, prolonged QT, QTc duration, and prolonged ventricular repolarization indices compared to non-smokers of matched age and gender. Conclusively, e-cigarette use is associated with negative cardiovascular effects like conventional cigarette smoking.